A BAD TEACHER AND THE BEST KING IN ELISABETH HAND’S ANNA IN THE KING - Satria Raditiyanto (Jurnal TEDC, 2016)
Deconstruction approach theory is a critical outlook concerned with the relationship between text andmeaning. It also as a strategy of rules for reading, interpretation, and writing. Deconstruction approachconsiders that language hasn’t a definite meaning or certain. Deconstruction essentially is a way how to read atext that subvert the notion (if it is only implicitly) that text has a foundation in the language system applicableto affirm the structure, wholeness, and meaning that has been stabilized (Abrams, 1981: 38). Deconstructivereadings, in contrast, treated works of art not as the harmonious fusion of literal and figurative meanings, butas instances of the intractable conflicts between meanings of different types. There is no idiom or linguisticforms meaning certain and definite. Deconstruction approach attacked the assumption that these structures ofmeaning were stable, universal, or a historical. This study was designed by using qualitative research model.Anna and the King novel will be analyzed by means of deconstruction approach with the title of my study : ABad Teacher and the Best King In Elisabeth Hand’s Anna and the King. My study are deconstruction researchmay consider by the multiple meanings of key words in a text, etymological relationships between words, andeven puns to show how the text speaks with different (and often conflicting) voices (Balkin 1990b; Balkin1989). This analysis according to the deconstruction analysis although it has been asserted that poststructuralism (in this case deconstruction is not an applicable method). I am sure it is possible to apply somebasic deconstructive moves to Elisabeth Hand text, which seems especially receptive, given its overtoppositions and emphasis on languageKey words: deconstruction approach theory, Anna and the King novel, qualitative research, post-structuralism.